Otimização da produção de amilases recombinantes para hidrólise de amido de mandioca visando produção de etanol - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Over the last 30 years, the industrial alcoholic fermentation processes have, significantly, increased the global profitability of Brazilian distilleries from 75-80% to 90-92% and reduced its production costs. Several factors contributed to the industrial processes improvement, including the identification, monitoring and the selection of yeast lineages. Starchy materials represent a very important and promising source of renewable biomass. To transform them into fermentable sugars, their degradation depends on the action of enzymes that can make the bioconversion of this material and it’s one of the main factors to be considered. The adopted strategy to develop this work was the culture medium optimization to the production of recombinant amylases through the Response Surface Methodology (RSM) based on the Rotational Central Composite Design (RCCD) which was also used to optimize the solids and the enzymatic loads to increase the glucoses releases and the enzymatic hydrolysis yield; concentration by tangential ultrafiltration in membranes; evaluation of the hydrolysis through the fermentation and analysis of the final product by gas chromatography. In this context, the present study aimed to optimize a production of recombinant amylases for hydrolysis of starchy resources aiming the starch alcohol production. The hydrolyzate of the cassava starch Manihot esculenta Crantz, the used starch source, have been obtained by the recombinant amylases utilization, being a cloned α-amylase from Bacillus licheniformis and a cloned glucoamylase from Aspergillus awamori both expressed in Pichia pastoris GS115, derived from previous works of our research team. The obtained hydrolyzate was fermented by a commercial Saccharomyces cerevisiae inside commercial systems named fermentometers. The optimal solid loads and enzyme blend loads set by RSM was 458,1 g/L and 19,15 μL/g of starch, respectively, and by these conditions was obtained (330 ± 4) g/L of glucose, corresponding to a hydrolysis yield of 89,36%. The hydrolyzate resulted in a concentration of 64,62 g/L of ethanol corresponding to 86% of conversion in 10h fermentation, with the fermentative hydrolysis (FH) at 86,16%, volumetric productivity (QP) 6,46 g/Lh and a yield factor in consumed substrate (YP/S) of 0,431g/g.
Keywords: Bioetanol - Produção; Biocombustíveis; Mandioca como combustível; CIENCIAS BIOLOGICAS; Etanol; Biomassas; Amilases recombinantes; Fermentação